2017
DOI: 10.1107/s1600576716018768
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous self-standing curved monocrystals, obtained using sandblasting, to be used as manipulators of hard X-rays and charged particle beams

Abstract: A technique to obtain self-standing curved crystals has been developed. The method is based on a sandblasting process capable of producing an amorphized layer on the substrate. It is demonstrated that the amorphized layer behaves as a thin compressive film, causing the curvature of the substrate. This procedure permits the fabrication of homogeneously curved crystals in a fast and economical way. It is shown that a sandblasted crystal can be used as an X-ray optical element for astrophysical or medical applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…PLSB was bent via the sandblasting method (Camattari et al, 2017), while PLCF was bent by the application of a carbon fibre composite (Camattari et al, 2014). Sandblasting is a mechanical process, which consists in driving a stream of abrasive material against a sample through a pressurized fluid, usually compressed air.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…PLSB was bent via the sandblasting method (Camattari et al, 2017), while PLCF was bent by the application of a carbon fibre composite (Camattari et al, 2014). Sandblasting is a mechanical process, which consists in driving a stream of abrasive material against a sample through a pressurized fluid, usually compressed air.…”
Section: Sample Preparationmentioning
confidence: 99%
“…For both samples the osculating circle lies on the polished side of the crystal (Camattari et al, 2017(Camattari et al, , 2018, i.e. they are bent to the opposite side with respect to the machined surface.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…CDP crystals have been simulated. In order to obtain crystals featuring CDPs, a promising technique could be the sandblasting method (Camattari et al 2017). Indeed, it was demonstrated that sandblasting a crystal through a flux of abrasive material produces on the surface of the crystal itself a thin damaged layer that behaves as a tensile film, allowing the precise curvature of the substrate.…”
Section: Simulationsmentioning
confidence: 99%
“…Another technique consisted of patterning a thin film of strained silicon nitride on a silicon monocrystal to generate an undulated structure [13]. Another technique consisted on sandblasting the two major surfaces of a crystal to produce a patterned amorphized layer capable of undulating the sample [14]. Sandblasting is a mechanical process consisting in driving a stream of abrasive material against a sample through a pressurized fluid, usually compressed air.…”
Section: Introductionmentioning
confidence: 99%